Exercise approaches to enhance physical function and perceived health in community-dwelling older adults - Coletta, Giulia (My University, 2024)
Age-related diseases such as sarcopenia (loss of muscle mass, strength, and function) and frailty are common in older adults with reduced physical mobility and, without mitigation, may lead to functional dependence, hospitalization, premature morbidity, and mortality. One approach to alleviate the secondary consequences associated with sarcopenia is through strengthening exercises. Unfortunately, participation rates in the prescribed amounts of exercise, let alone strengthening activities, among older populations are low. Older adults face several barriers to exercise participation, including a lack of access to facilities, transportation, supervision, poor weather concerns, and a fear of injury. Therefore, novel exercise approaches must be developed to improve older adults’ engagement in exercise. The purpose of this dissertation was to explore novel exercise approaches for community-dwelling older adults to improve their physical function and perceived health. In study 1, we investigated the preliminary effectiveness and feasibility of a home-based, group, synchronous online exercise program delivered by health professionals through quantitative and qualitative methods. We found the synchronous online exercise intervention had preliminary effectiveness in improving symptoms of depression and life-space mobility and was shown to be feasible. Participants perceived physical and mental health benefits and identified that the health professionals contributed to the perceived safety of the intervention. In study 2, we deepened our understanding of community-dwelling older adults’ perceptions and experiences of exercise with our live online exercise program. Our findings suggest that older adults found that our synchronous online exercise program attenuates common barriers to exercise, including removing concerns about transportation and poor weather, and improves the ease of participation from their desired training location. In study 3, we employed an 18-week faded contact group-based resistance band functional training study for preclinically mobility-limited community-dwelling older adults. We determined that the resistance bands training program demonstrated that participants exceeded minimal clinically important differences in physical function assessed by the short-performance physical battery and the 4m walk test for the intervention group. Together, these studies contribute novel insights into different exercise approaches leveraging live videoconferencing technologies, group-based classes, transitional participant contact, and the use of health professionals to deliver feasible programs for engaging older adults in exercise programs. This work is novel and contributes new knowledge; it also lays a foundation for further larger trials of programs like the ones described in this thesis.
Keywords: Exercise; Older Adults; Sarcopenia; Physical Function; Resistance Training; Mixed-methods; Synchronous